A preliminary study on the toxic effect of makabuhay (Tinoshpora numphii) aqueous stem extract on Oreochromis niloticus fingerlings. - Dignadice, Zelle Benueza (1996.)
The toxic effect of "makabuhay" (Tinosphora rumphii) aqueous stem extract on Oreochromis niloticus fingerlings was studied for a duration of 96 hours. Three replicates were done with the test animals exposed to the following concetrations of the toxicant: 0 (control), 25, 50, 75, and 100 ppt. The most potent concentration was 100 ppt. After 96-hour, the resulting LC50 was 48.91 ppt. with 3.76 - 4.01 95 Confidence Interval. The concentrations: 50.75 and 100 ppt had a significant-effect on the mortality of the fingerlings. Physico-chemical parameters such as temperature, pH, salinity, DO and ammonia were recorded and were found to be within tolerable range for the fingerlings.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Fingerlings -- Tinoshpora numphii; Fingerlings -- Oreochromis niloticus